Health Beliefs and Practices of African Immigrants in Canada. (December 2016) - Cooper Brathwaite, Angela; Lemonde, Manon
A purposive sample of 14 immigrants living in Ontario, Canada, participated in two focus groups. The researchers used semi-structured interviews to collect data and five themes emerged from the data: beliefs about diabetes were centered on diverse factors, preserving culture through food preferences and preparation, cultural practices to stay healthy, cultural practices determined number of servings of fruit and vegetables per day, and engaging in physical activity to stay healthy. Findings indicated how health beliefs and cultural practices influenced behavior in preventing type 2 diabetes (T2D). Future research should focus on other high-risk minority groups (South Asian, Caribbean, and Latin American) to examine their health beliefs and cultural practices and use these finding to develop best practice guidelines, which should be incorporated into culturally tailored interventions.